2020
DOI: 10.1038/s41598-020-72292-0
|View full text |Cite
|
Sign up to set email alerts
|

Repeated intravesical injections of platelet-rich plasma improve symptoms and alter urinary functional proteins in patients with refractory interstitial cystitis

Abstract: Repeated intravesical injections of autologous platelet-rich plasma (PRP) have been shown to improve symptoms in patients with interstitial cystitis/bladder pain syndrome (IC/BPS); however, there is a paucity of objective evidence of the effectiveness of this therapy. In this study, we investigated the changes in urinary markers after PRP treatment. Forty patients with IC/BPS who were refractory to conventional therapy received four injections of PRP at monthly intervals; 10 mL PRP solution with 2.5 times the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 33 publications
(49 reference statements)
0
36
0
1
Order By: Relevance
“…Furthermore, the authors compared the results obtained with those of a control group whose subjects did not have bladder symptoms. Only the urinary VEGF level was higher in patients with IC/BPS at baseline; however, it was lower after PRP injection in patients with IC/BPS than in the controls (all, p < 0.0001) [21].…”
Section: Clinical Trialmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, the authors compared the results obtained with those of a control group whose subjects did not have bladder symptoms. Only the urinary VEGF level was higher in patients with IC/BPS at baseline; however, it was lower after PRP injection in patients with IC/BPS than in the controls (all, p < 0.0001) [21].…”
Section: Clinical Trialmentioning
confidence: 76%
“…Jiang et al [21]. searched for objective evidence regarding the efficacy of PRP injections in a subsequent study.…”
Section: Clinical Trialmentioning
confidence: 99%
“…A previous pilot study by the authors applying PRP in the treatment of IC has revealed that repeat intravesical PRP injections could improve clinical symptoms in patients with IC/bladder pain syndrome (BPS) 19 . The urine biomarkers such as NGF, PDGF‐AB, matrix metalloproteinase‐13 (MMP‐13), and vascular endothelial growth factor (VEGF) showed significant changes after three PRP injections 28 . These results provided evidence of the changes in urinary protein expressions to support the therapeutic effects of PRP in the treatment of IC/BPS, suggesting intravesical PRP treatment could improve urothelial health in patients with IC/BPS refractory to conventional therapy through promoting cell proliferation, migration, differentiation, and angiogenesis 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenesis of IC/BPS are multifactorial and several studies have attributed to the exhibited symptoms to an increase in inflammatory cells infiltration, hypoxia-inducible factor-1α, VEGF, and apoptosis 3 , 4 noted on histopathological and molecular studies. Thus, the treatment of IC/BPS aiming at regulation of inflammatory reaction and regeneration or repair of urothelium defect could be an attractive option for the management of refractory IC/BPS.…”
Section: Introductionmentioning
confidence: 99%